Culturas náuticas e ciências sociais no Brasil: um balanço da produção antropológica, histórica e arqueológica (Parte 2) - Leandro Domingues Duran (Navigator)
The present article provides the second part of an analysis about the history of academic research carried on in the field of Anthropology, History and Archaeology, specially referring to those researches focused on the study of different nautical cultural traditions developed in several aquatic environments in Brazil. The article outlines the main thematic choices pointing out the limits on their approaches. This second part focus on the studies developed in the field of History and Archaeology as well as provides a brief final consideration about the overall production in the different mentioned areas of knowledge